The nomenclatural status of “Anoplophallus maculatus” Cope, 1895, its consequences on the systematics of Lycodon subcinctus auctorum, and the description of a new species (Squamata: Colubridae) - Nguyen, Tan Van; Lee, Justin L.; Pauwels, Olivier S. G.; Kennedy-Gold, Stevie R.; Poyarkov, Nikolay A.; David, Patrick; Vogel, Gernot (Zootaxa, 2024)
The Malayan banded wolf snake, Lycodon subcinctus (F. Boie, 1827) has a complicated taxonomic and nomenclatural history. For almost a century, the combination Anoplophallus maculatus Cope, 1895 has been applied to populations of L. subcinctus from southern China, with various authors recognizing the taxon maculatus as a subspecies (i.e., Lycodon subcinctus maculatus) or junior synonym. A recent study that proposed the elevation of Chinese L. subcinctus to species rank (as Lycodon “maculatus”) prompted us to re-investigate several nomenclatural issues relevant to Anoplophallus maculatus that have not been fully addressed in the literature. We show that Anoplophallus maculatus was not described as a new species, and actually refers to Megalops maculatus Hallowell, 1861, a Neotropical snake currently known as Leptodeira maculata (Dipsadinae). As a consequence, populations of L. subcinctus recently recognized as Lycodon “maculatus”, have no valid binomen applied to them. To resolve this issue, we provide a new species name for populations of L. subcinctus from China and include a morphological description based on specimens collected across all of mainland Southeast Asia. The new species, Lycodon neomaculatus sp. nov., occurs well outside of southern China, and inhabits Indochina (Cambodia, Laos, Thailand, Vietnam) and eastern Myanmar. Lycodon neomaculatus sp. nov. is distinguished from both L. sealei and L. subcinctus by subtle differences in adult dorsal color pattern and body scalation. The distributions of L. neomaculatus sp. nov. and L. subcinctus sensu stricto appear to be allopatric, and the Isthmus of Kra region in peninsular Thailand may act as a biogeographic filter separating the two species.